Conversion of reverse osmosis membranes into metal-free carbocatalyst for electrochemical syngas production - Chen, Jie (2022)
Reverse osmosis (RO) membranes are widely employed in water treatment, raising needs for developing spent membrane modules waste management system. This study investigates the upcycling of spent RO membranes through a facile two-step process into functional carbocatalysts that can be successfully applied in electrochemical syngas production with tunable CO/H2 ratios. At first, the spent RO membrane module was pyrolyzed at 600 °C into char. The obtained char demonstrated poor electrochemical performance. Therefore, the char was further subjected to a high temperature (700–1000 °C) doping with melamine. The presence of melamine and the heat treatment were found crucial to convert the char into electrochemically active carbocatalysts. The prepared carbocatalysts showed an enhanced electrochemical reduction capability towards CO2 and H2O producing a mixture of CO and H2. The higher heat treatment temperature of the char increased the carbonization degree and the relative content of graphitic N groups. As a result, the carbocatalyst heat-treated at 1000 °C exhibited the highest CO selectivity with Faradaic efficiency up to 70.1%. Moreover, CO/H2 volumetric ratio of syngas could be easily regulated from 3:1 to 1:10 by adjusting applied electrochemical potentials. In this respect, the proposed two-step approach for the carbocatalyst synthesis could be a feasible strategy for addressing the RO membrane waste and producing syngas with suitable composition for a variety of industrial applications.